The spectrum of BRCA mutations and characteristics of BRCA‐associated breast cancers in China: Screening of 2,991 patients and 1,043 controls by next‐generation sequencing - Lang, Guan‐Tian; Shi, Jin‐Xiu; Hu, Xin; Zhang, Chen‐Hui; Shan, Ling; Song, Chuan‐Gui; Zhuang, Zhi‐Gang; Cao, A‐Yong; Ling, Hong; Yu, Ke‐Da; Li, Shan; Sun, Meng‐Hong; et al. (International journal of cancer, 2017)
To characterize the prevalence of BRCA mutations and characteristics of BRCA carriers in China and to update the clinical recommendations for BRCA testing, we conducted a wide screen for BRCA mutations using next‐generation sequencing (NGS). A total of 4,034 Chinese subjects were screened for germline BRCA1/2 mutations, including 2,991 breast cancer patients and 1,043 healthy individuals from the community enrolled as controls. We developed an NGS‐based approach to perform BRCA1/2 screening. BRCA mutations were identified in 9.1% (232/2,560) of cases with at least one risk factor, in 3.5% (15/431) of sporadic patients and in 0.38% (4/1,043) of healthy controls. The mutation frequency ranged from 8.9 to 15.2% in cohorts with a single risk factor to 16.6–100% in groups with multiple risk factors. We identified 70 novel BRCA mutations. A high frequency of BRCA1 c.5470_5477del was detected, accounting for 13.9% (16/115) of the BRCA1 mutations detected in our study. Clinical characteristics such as family history, invasive carcinoma, negative human epidermal growth factor receptor 2 (HER2), high Ki67 index, lymph node status, and high tumour grade were closely related to BRCA mutations. BRCA2 carriers had poorer disease‐free survival among HER2‐ or hormone receptor‐positive patients (hazard ratio = 1.892; 95% confidence interval: 1.132–3.161; p = 0.013). This study shows that BRCA mutation carriers could be frequently identified among breast cancer patients with multiple risk factors. Importantly, we established an NGS‐based pipeline for BRCA1/2 testing in clinical practice and strongly suggest that breast cancer patients of premier‐ and moderate‐grade risks receive BRCA1/2 mutations testing in China. What's new? Chinese women carrying BRCA mutations are at lower risk of breast cancer compared with female carriers in other countries, a phenomenon that may explained by associations between ethnic background and specific BRCA variants. Little is known, however, about BRCA1/2 mutation prevalence and related clinical characteristics among Chinese women. Here, overall BRCA1/2 mutation frequency was found to be 9.1% in Chinese breast cancer patients, compared with 0.38% in healthy Chinese controls, based on next‐generation sequencing (NGS) analyses. BRCA mutations were closely associated with clinical characteristics, including family history and tumour grade. BRCA mutation carriers could be readily identified by NGS testing.